The Effectiveness of TURBODENT Educational Media in Improving Toothbrushing Skills in 5-6-Year-Old Children at Raden Paku Kindergarten, Surabaya - Azzahra Septiana Nur Annisa; Bambang Hadi Sugito; Ida Chairanna Mahirawatie; Isnanto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Toothbrushing skills in preschool children are crucial for dental health. However, children often struggle to apply the correct techniques. A preliminary study conducted on 5-6-year-old children at Raden Paku Kindergarten in Surabaya revealed that most of them had inadequate skills in performing toothbrushing movements. Educational media serve as an effective tool for conveying messages to enhance toothbrushing skills. Efforts to improve these skills can be implemented using the TURBODENT (Try Using Box Dental) media. This study aims to evaluate the effectiveness of the Try Using Box Dental media on the toothbrushing skills of 5-6-year-old children at Raden Paku Kindergarten in Surabaya. This research employs a quasi-experimental method with a pretest-posttest control group design. The study sample consists of 40 children aged 5-6 years, divided into two groups: the intervention group and the control group. Data collection instruments include an observation checklist for toothbrushing skills. Data analysis techniques involve the Wilcoxon test and the Mann-Whitney test. Results: the Wilcoxon test for the intervention group shows a p-value of 0.000, while the control group has a p-value of 1.000. The Mann-Whitney test results in a p-value of 0.000 or < 0.05. The study concludes that the Try Using Box Dental media is effective in enhancing the toothbrushing skills of 5-6-year-old children at Raden Paku Kindergarten in Surabaya.